Analysis of a failed rocker arm shaft of a passenger car engine. (April 2016) - Nassef, G.A.; Elkhatib, A.; Yakout, Mostafa
Highlights: Failure of a rocker arm shaft of a passenger car. The non-uniform cooling during quenching causes failure. The repeated loading during service causes fatigue. The lower fracture toughness of the martensite causes rapid crack propagation. Abstract: This paper investigates the failure of a rocker arm shaft of a passenger car. The shaft failed by brittle fracture across one of the four holes supporting the shaft into the cylinder head. The running distance of the engine just before failure was 40, 626 km. Visual examinations of etched sections of the failed shaft and a new one revealed four distinct zones of darker etching appearance. These zones correspond to the four locations where the rocker arms fit the shaft. Microscopic observations of the failed shaft revealed that the four dark-etching areas are surface hardened zones of martensitic microstructure. Furthermore, scanning the microstructure along the failed shaft showed that the heat treatment was so mistakenly extended by excessive heating so that the structure of the shaft near the supporting holes contains considerable content of martensite phase. This conclusion has been confirmed by the results of hardness measurements along the surface of the shaft. Microscopic investigations of the failed shaft revealed the presence of microcracks close to the supporting holes. These cracks may have been induced in the shaft by the non-uniform cooling during quenching in the course of heat treatment, or may be nucleated by repeated loading during service. This premature failure has occurred by the rapid crack propagation because of the lower fracture toughness of the martensite.